I believe the numbers are 63 and 65.
Answer:
Student B is correct
Student A failed to distribute -4 and -6 when opening the brackets in the first step
Step-by-step explanation:
The solution Student A gave was:
2x - 4(3x + 6) = -6(2x + 1) - 4
2x - 12x + 6 = -12x + 1 - 4
-10x + 6 = -12x - 3
2x = -9
x = -4 _1 2 ( -4 1/2)
The solution Student B gave was:
2x - 4(3x + 6) = -6(2x + 1) - 4
2x - 12x - 24 = -12x - 6 - 4
-10x - 24 = -12x - 10
2x = 14
x = 7
Student B is correct.
Explanation of the error:
Student A failed to distribute -4 and -6 when opening the brackets in the first step.
That is,
2x - 4(3x + 6) = -6(2x + 1) - 4
To open this bracket, we will distribute, -4 and -6 so that we get
2x (-4 × 3x) + (-4 × +6) = (-6×2x) + (-6 × +1) - 4
Then we will get
2x -12x -24 = -12x -6 -4
Adding the like terms
-10x - 24 = -12x - 10
Collecting like terms
-10x + 12x = -10 + 24
∴ 2x = 14
x = 14 / 2
Hence,
x = 7
I am not exactly sure, but I am almost positive it is a spere
The average speed, in km/minute, of the train is 2.79 km/minute
<h3>Calculating average speed </h3>
From the question, we are to calculate the average speed in km/minute
From the given information,
Distance travelled = 503 km
Time taken = 3 hours = 3 × 60 minutes = 180 minutes
Using the average speed formula,
Average speed = Distance / Time
∴ Average speed of the train = 503 / 180
Average speed of the train = 2.79 km/minute
Hence, the average speed, in km/minute, of the train is 2.79 km/minute
Learn more on Calculating average speed here: brainly.com/question/12025128
#SPJ1